2012
DOI: 10.1016/j.jval.2011.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Eliciting Public Preference for Health-Care Resource Allocation in South Korea

Abstract: The results showed that Koreans support not only health maximization but also equal opportunity, fair resource allocation, and equality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 15 publications
(16 reference statements)
0
16
1
Order By: Relevance
“…Of these 15 studies, 5 studies reported using content analysis 36,4245 and 2 studies (2%) reported using framework analysis. 46,47 Other analytical approaches included the use of grounded theory methods such as the constant comparative method 48 and open-ended coding. 49 Three studies detailed the use of specialist qualitative software: 2 studies 36,50 (2%) used NVivo, and 1 study 51 used Atlas.ti.…”
Section: Resultsmentioning
confidence: 99%
“…Of these 15 studies, 5 studies reported using content analysis 36,4245 and 2 studies (2%) reported using framework analysis. 46,47 Other analytical approaches included the use of grounded theory methods such as the constant comparative method 48 and open-ended coding. 49 Three studies detailed the use of specialist qualitative software: 2 studies 36,50 (2%) used NVivo, and 1 study 51 used Atlas.ti.…”
Section: Resultsmentioning
confidence: 99%
“…The burden and prevalence of diseases are among the most influential criteria for allocating health resources. All around the world, policymakers consider the severity of illness as an important criterion for prioritizing (31). The burden of diseases, which includes the most important causes of death and disability, is a highly valuable indicator for planning health interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Severity of illness at the individual level is widely accepted as primary importance to be adopted with the effectiveness of treatment in diverse settings. Use of severity as a priority indicator has been seen in countries such as South Korea [ 59 ] and Uganda [ 60 ], and has established significance in developed countries through its use in many National Health Services (such as the Norwegian, Finnish, French, Spanish, German and Swedish NHS) [ 61 ]. Its major presence (75% of the identified articles) might be due to its relatively easy measurement and link with measurable outcomes with associated costs and health effects.…”
Section: Discussionmentioning
confidence: 99%